EAR-20 peptide, a novel NMDA receptor positive allosteric modulator - García-Díaz, Roberto; Castellanos, Aida; Miguez-Cabello, Federico; Picañol, Javier; Pérez-González, Anna Priscil·la; Gratacòs-Batlle, Esther; Vega-Castro, Nohora; Altafaj, Xavier; Reyes-Guzmán, Edwin A.; Reyes-Montaño, Edgar A.; Gasull, Xavier; Soto, David (Frontiers in Pharmacology, 2025)
Allosteric modulation of ligand-gated ion channels provides a powerful mechanism to fine-tune their activity without competing with endogenous ligands. In the case of NMDA receptors (NMDARs), which are critical for excitatory neurotransmission and synaptic plasticity, allosteric modulators represent potential therapeutic tools, particularly in conditions involving NMDAR hypofunction. Here, we characterize EAR-20, a 17-amino-acid peptide derived from the marine cone snail toxin Conantokin-G, as a novel positive allosteric modulator (PAM) of NMDARs. Using molecular docking, whole-cell and single-channel patch-clamp electrophysiology, and recordings in cultured hippocampal neurons, we show that EAR-20 enhances receptor function by increasing channel open probability and reducing desensitization, and can even activate NMDARs in the absence of exogenous glutamate and glycine, albeit to a lower extent. EAR-20 decreased desensitization, potentiating GluN1-GluN2A and GluN1-GluN2B receptors more than twofold, modestly enhanced (∼25%) GluN1-GluN2A-GluN2B tri-heteromers, and increased NMDAR-mediated currents in primary hippocampal neurons. Molecular docking identified a binding site at the GluN1-GluN2B interface, with Ser773 in GluN1 being critical for the modulatory effect. Importantly, EAR-20 partially rescued hypofunctional NMDARs carrying patient-derived loss-of-function mutations. Together, these findings identify EAR-20 as a novel subunit-dependent positive allosteric modulator with the potential to inspire the development of small molecules targeting the same binding site, offering proof of concept for therapeutic strategies to treat neurological and neurodevelopmental disorders.